Level of stress, anxiety, and depression symptoms among health sciences students in UiTM Puncak Alam Campus during COVID-19 pandemic / Nurul Al Syuhailin Mhd Zaki and Padma A. Rahman - Mhd Zaki, Nurul Al Syuhailin; A. Rahman, Padma (Faculty of Health Sciences, Universiti Teknologi MARA, 2022)
The coronavirus illness disease 2019 (COVID-19) epidemic has had a tremendous influence on people's life across the world, particularly after the World Health Organization proclaimed a worldwide pandemic in the second week of March 2020. This study aims were to determine the level of stress, anxiety and depression among health sciences students during the covid-19 pandemic in UiTM Puncak Alam Campus. The cross-sectional study was conducted in UiTM Puncak Alam at Selangor state. All the students studying from year 1 to year 4 and health science students aged 18 years old and above that willingly to participate in the study were included. The Depression, Anxiety, Stress Scale 21 (DASS 21) was used to determine the level of stress, anxiety and depression symptoms among health sciences students. Among 191 students enrolled in the study, majority 78 (40.8%0 were in the age group of 24-25 years old, 145 (75.9%) were females, 73 (38.2%) were studying in semester eight and 45 (23.6%) was from Environmental Health and Safety course with 169 (88.5%) was from a full-time mode of study. Results shown that 122 (63.9%) of the students reported having anxiety symptoms, 107 (56.0%) were reported with depression symptoms and 82 (42.9%) were reported with stress. The depression traits show majority of health sciences students were in moderate stage (16.8%). Majority of students were in mild stage (18.3% and 17.8%) for stress and anxiety traits. Occupational therapist could play a role in educating stress management techniques as the majority of the students had milder degrees of illness that needed to be addressed quickly before they manifested into severe versions.